Analisis Penerapan Birth and Death Process pada Teori Antrean Wizzmie Jimbaran - Ni Komang Viona Amelia Putri; I Gede Eza Purnama Putri; Ni Putu Dhea Angelita Dusak; I Gusti Ayu Made Srinadi; Made Ayu Dwi Octavanny (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
A queue is a condition where there is a delay in service due to busy service activity. Queues can occur at places that provide services, one of which is at places that provide food and beverage services. The fast food trend is growing rapidly. One of the restaurants providing fast food is Wizzmie Jimbaran. Queuing theory is used to determine optimization in decision making in queuing systems. This research purposed to determine the theory and queuing system, birth and death in queuing theory, queuing system model, the probability that there are zero people in the system, average arrival rate, average level of service to visitors, and to find out optimality of the queuing system at Wizzmie Jimbaran. From the results, it was found that a birth and death process occurred at Wizzmie Jimbaran queuing process with the M/M/3 queuing model and First In First Out (FIFO) service discipline. The average level of consumers waiting in queue is 1-3 queues. With the system utility level ranging at intervals that are not much different and the probability that there are zero people in the system recorded is less than 1. The time required for visitors in the system is 2-5 minutes and the time required for visitors in the queue is 1-5 minutes.